When "new" crops are not really new: California Indigenous communities and research and commercialization of elderberry - Sonja Brodt; Sabine Talaugon; Gwenael Engelskirchen (California Agriculture)
The article “Native blue elderberry in hedgerows bridges revenue and conservation goals” focuses on the commercial potential of western blue elderberry (Sambucus nigra ssp. cerulea) plantings, primarily on private farmland in California. While blue elderberry is little known as a commercial agricultural crop, it is anything but new to the Indigenous people of this place. Many of the nearly 200 tribes that live in California have been in relationship with elderberry, and the land it grows on, since time immemorial, seeing all living beings as their own kin, rather than merely utilitarian resources. For non-Indigenous farmers and researchers working with elderberry, it is important to be aware of our state’s history of land dispossession and non-Native land management practices, which have often diminished California Native peoples’ access to and sovereignty over traditional foods, medicines and cultural materials.